JAEPL, Vol. 9, Winter 2003-2004 - Katie S. Fleckenstein; Linda T. Calendrillo (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
Essays Kilian McCurrie. Spiritual Identities, Teacher Identities, and the Teaching of Writing. Through a case study, this article examines the ways teacher identity and spiritual identity intersect in the teaching of writing. By showing that a teacher's pedagogy is prodoundly informed by a basic spiritual disposition, the author offers a view of teaching that is often neglected in studies of teacher identity. Robert Root. The Experimental Art. Nonfiction is an experimental art, as contemporary examples make clear, and writing teachers need to show students both how meaning arises from writers' experiments with material and also how form from writers' experiements at representing meaning. Candance Walworth. Engaged Buddhism & Women in Black: Our Grief Is Not a Cry for War. This paper explores principles, practices, and manifestations of engaged Busshism in the United States. It includes a personal narrative based on the author's participation in Women in Black (a silent, symbolic protest against war) and classroom stories based on the author's experience teaching at a Buddhist-inspired university. Laura Milner. Compos(t)ing Loss: Transformation in the Telling. Using composting as a metaphor, this author examines the transformative protential in writing about and bearing witness to stories of loss, particularly the death of a parent. Cristina Vischer Bruns. Encounters: Relationship in the Study and Teaching of Literature. While trends in the teaching of literature of the last few decades may seem at odds with one another, the thread that can weave them together is a recognition of relationship among readers, text, author, and other readers. Kia Jane Richmond. An Unspoken Trust—Violated. Reflecting on our decisions in the classroom, both when we are honest with our students & when we are not, can offer teachers opportunities for growth and change. Carolyn L. Piazza and Christine Jecko. Multiple Forms of Prewriting in Elementary Writing Literature. Multisensory prewriting invitations (creative visualizations, art, music, dreams, and mediations) affect writing fluency and idea generation in the first draft writing of elementary students. W. Keith Duffy. Community, Spirituality, and the Writing Classroom. From a spiritual perspective, this article critiques the concept of community as defined by scholars of rhetoric and composition; the author suggests that our experience of community in the writing classroom cab be enhanced if we strike a balance between doing and being. Helen Walker. Connecting. Jim Super—Fearless Pamela Hartman—English? I'd Rather Read A Book Nancy Myers—B Andrea Siegel—Walking the Talk, Breathing the Breath Traci L. Merritt—The Day Jenny Died Susan A. Schiller—Touched by the Spirit in AEPL Topics Wilma Romatz—On the Delicate Art of Teaching Reviews Dale Jacobs. The Energy to Teach (Donald H. Graves, 2001) Stan Scott. Writing with Elbow (Pat Belanodd, 2002) Sue Hum. Unfolding Bodymind (Brent Hocking, Johnna Haskell, Warren Linds, 2001) Lita Kurth. The Unconscious (Athony Easthope, 1999)